Psychological impacts of COVID-19 on the general population of Iran - Abolfathi Momtaz, Yadollah; Zanjari, Nasibeh; Delbari, Ahmad; Foroughan, Mahshid (Negah Institute for Social Research and Scientific Communication, 2024)
Background: During the COVID-19 pandemic, the main focus of studies was on physical impact of the disease, while psychological impacts were mainly neglected. Identifying the psychological impacts of the COVID-19 pandemic on the general population can help in planning and preparing for future pandemics. The current study aims to investigate the psychological impacts of the COVID-19 pandemic on the general population of Iran. Materials and Methods: This cross-sectional survey study that was conducted online on 1735 Iranian people from April 21 to June 21, 2021. Perceived feelings during the COVID-19 pandemic were measured by Reynolds’s self-report tool. The collected data were analyzed using descriptive statistics (frequency and percentage) and inferential statistics including chi-square test and independent t-test in SPSS software, version 22. The significance level was set at 0.05. Results: The mean age of the respondents was 34.62±11.86 years. The most frequent perceived feelings were boredom (n=764, 44.0%), nostalgia (n=704, 40.6%), worry (n=613, 35.3%), and nervousness (n=591, 34.1%). Females, younger people, unemployed people, unmarried people, and those living in the urban areas experienced significantly higher levels of negative feelings. Conclusion: The psychological impact of the COVID-19 pandemic on Iranian people is high, particularly among female, unmarried, and unemployed people. Therefore, supportive and psychological interventions during the pandemic and psychological rehabilitations after the pandemic are needed.